2011
DOI: 10.1063/1.3658960
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and fast shift in reflection band of a cubic blue phase in a vertical electric field

Abstract: Two electro-optical phenomena of liquid-crystal blue phase with cubic lattice structure—(1) a fast and reversible shift in reflection band and (2) a phase transition from blue phase to chiral nematic phase—are observed in this study. By increasing the magnitude of a vertical electric field, the reflected wavelength of the blue phase can be shifted to a longer wavelength in a range of 80 nm within a few ms. This reflection band shift is induced by the reorientation of liquid-crystal molecules constructing doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…As the applied voltage was increased, the various colors switching of blue, green, and red corresponding to a continuous shift of Bragg wavelength under the electric field were observed. The color switching times from green to red have been experimentally proven to be of millisecond order 34, 88. The shift ranges and the switching times for BPs were comparable to those of polymer‐stabilized N* systems 89, 90…”
Section: Resultsmentioning
confidence: 85%
“…As the applied voltage was increased, the various colors switching of blue, green, and red corresponding to a continuous shift of Bragg wavelength under the electric field were observed. The color switching times from green to red have been experimentally proven to be of millisecond order 34, 88. The shift ranges and the switching times for BPs were comparable to those of polymer‐stabilized N* systems 89, 90…”
Section: Resultsmentioning
confidence: 85%
“…From these previous studies, we can conclude the following experimental characteristics of BPIII: (1) BPIII is stabilized by strong chirality and usually occupies a temperature range of $0.1 C just below the isotropic phase; 4 (2) BPIII is strongly optically active; (3) BPIII reflects a very weak and broad region at short wavelengths, which depends on the chirality of the liquid crystals; 5 (4) the latent heat of BPIII is larger by an order of magnitude than other phase transitions 6 such as N* to BPI or BPI to BPII; and (5) BPIII is only weakly affected by moderate electric fields; 3,5,6 (6) because of the Kerr effect, BPIII can be switched between optical isotropy and anisotropy under an in-plane field. 7,8 In our previous study, 9 we found that for cubic BPI the reflection spectra can be changed by applying an external field. As the external field increases, the reflected peak shifts to a long or short wavelength, depending on the directions of the electric field and lattice surface and the dielectric anisotropy of the LC materials.…”
Section: Introductionmentioning
confidence: 88%
“…5 The wavelength shift of BPI in the field can be larger than 40 nm, and the intensity of the reflection does not change obviously. 9 This means that BPI can be used as a wavelength-tunable reflector.…”
Section: Introductionmentioning
confidence: 99%
“…According to arrangements of the DTCs and the disclination lines, three structurally distinct types of blue phase are identified: BP III, BP II, and BP I, appearing in order of decreasing temperature from the isotropic phase. BPIII exhibits a disordered structure [1,2]; BPI and BPII display high-ordered lattice structures, giving rise to unusual physical properties, including a fast electro-optical response [3,4] and Bragg reflection of visible light [5]. These characteristics make BPI and BPII very promising materials for prospective applications in novel displays and photonic technology [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%